The sequential therapy for non-infectious scleritis: A case report - Xiaoxiang Xie; Pan Jiang; Xuxu Li; Jinli Ru (SAGE Open Medical Case Reports)
Scleritis results from an inflammatory response in the sclera and can be associated with a variety of infectious and non-infectious ocular and systemic diseases. It can cause vision loss, uveitis, high intraocular pressure and other complications, resulting in poor prognosis. There are no reports of non-infectious scleritis in children. Herein, we describe a case of sequential tocilizumab treatment on tofacitinib in a child with non-infectious scleritis. Extensive examinations ruled out the cause of infection, and the previous conventional glucocorticoid treatment was effective, but the disease recurred during drug reduction. Tocilizumab and tofacitinib successfully cured the patient, glucocorticoids were stopped, and all drugs were stopped 2 years later. This report provides a new diagnosis and treatment method for clinicians.